TB Incidence Trends in the Kingdom of Saudi Arabia within the GCC, EMR, and MENA Regions, to Achieve the WHO and UN’s SDG End TB Strategy Targets - Mazin Barry (Journal of Epidemiology and Global Health)
Abstract Objectives To assess the tuberculosis (TB) incidence trends, between 2000 and 2023, in the Kingdom of Saudi Arabia (KSA), in comparison to that in different geopolitical regions where the KSA is commonly included within, and to determine whether the KSA achieved the World Health Organization (WHO) and the United Nations (UN) Sustainable Development Goals (SDGs) End TB Strategy milestones and targets, including the reduction of the total TB incidence by 20% in 2020 compared to that of 2015. Methods This is a retrospective observational study on the TB incidence per 100,000 population arising in a given year as reported annually to the WHO. The data was extracted from the WHO indicator dataset. TB incidence data from the KSA, the World, the Gulf Cooperation Council (GCC), the Eastern Mediterranean region (EMR), and the Middle East and North Africa (MENA) region were included. Descriptive analysis and chi-square test were used to compare incidence differences and their statistical significance. Results The TB incidence per 100,000 population in KSA in 2023 was 8.4 (95% uncertainty interval [UI]: 7.6–9.3), in 2020 it was 8.7 (95% UI:7.7–9.6), in 2015 it was 12 (95% UI: 11–13), in 2000 it was 23 (95% UI: 21–26). Compared to 2023, the reduction from 2000, 2015, and 2020 were − 14.6 (63.5% p < 0.01), − 3.6 (30%), and − 0.3 (3.4%), respectively. Compared to 2015, the reduction in 2020 was − 3.3 (27.5%). For 2023, compared to the GCC countries, the KSA had the second lowest incidence after the United Arab Emirates (UAE), which was − 7.6 less than KSA (p < 0.01). The incidence in Qatar was the highest, which was + 26.6 higher than KSA (p < 0.01). Compared to the MENA and EMR, only Jordan had a lower incidence, which was − 5.0 less than KSA. Pakistan had the highest incidence rate and the highest difference from the KSA by + 268.6 (p < 0.01). Conclusion TB incidence trends are decreasing in KSA, and it is among the top three regional countries with the lowest incidence rates. Compared with 2015, KSA exceeded the 20% milestone by achieving a 27.5% reduction in 2020. The KSA is heading towards achieving the WHO and UN’s SDG End TB Strategy targets of a 50% reduction by 2025, 80% by 2030, and 90% by 2035, to fulfill the vision of a world free of TB.